Curcumin biosynthesis from ferulic acid by engineered Saccharomyces cerevisiae - Costa, João Manuel Rainha (2022)
Background and Goal Curcumin is a polyphenolic compound found in Curcuma longa. This bioactive molecule has several reported health-benefit effects, being the anticarcinogenic activity among the most promising ones. However, curcumin extraction from natural sources is hampered by impure products obtained from harsh chemicals and limited by plant seasonality and high prices. Therefore, curcumin heterologous production emerged as an interesting alternative. Escherichia coli has been explored as chassis but the implementation of the pathway in Saccharomyces cerevisiae can have several advantages, including its generally regarded as safe status. Hence, S. cerevisiae was engineered for the first time to produce curcumin from its precursor ferulic acid. Methods and Results The enzymes 4-coumarate-CoA ligase (4CL1) from Arabidopsis thaliana or feruloyl-CoA synthetase (FerA) from Pseudomonas paucimobilis and type III polyketide synthases (PKSs) from Oryza sativa or C. longa were expressed in BY4741 strain. To avoid ferulic acid deviation, the gene FDC1 coding a ferulic acid decarboxylase was deleted. The maximum curcumin titer was obtained with FerA combined with C. longa PKSs (2.7 mg L1). Conclusions and Implications Up to our knowledge, this is the first work reporting the expression of a feruloyl-CoA synthase and also curcuminoid biosynthetic enzymes in S. cerevisiae, and consequently, curcumin production.